Engaging in the good with technology: a framework for examining positive technology use - Andrew Villamil; Saeideh Heshmati (Frontiers in Psychology, 2023)
The focus on the negative side of technology has become a prominent factor in the understanding of the interactions between humans and technology. However, there is a positive side to technology use that has been less investigated in scientific research. Well-being researchers have determined that it is not just the absence of negative emotions or experiences, but rather the presence and frequency of positive ones that matter most. Therefore, despite the scarcity of research on the positive side of technology, the present conceptual paper focuses on how technology may be used for the good to produce psychological benefits (e.g., greater happiness, lower loneliness, higher peer endorsement). Based on existing literature, we posit at least three directions for good interactions with technology: (1) “seeing good” by focusing on positive visual cues through technology use; (2) “feeling good” by focusing on good feelings that arise from technology use; and (3) “doing good” by focusing on positive actions that can be enacted via technology use. Based on the synthesis of these three components, we propose a framework for technology laden engagement in the good, dubbed as, the Engagement in the Good with Technology (EGT) Framework. Through this framework, we explain how these three distinct aspects of seeing, feeling, and doing good can co-occur and be interrelated, and in turn potentially lead to upward spirals of positive outcomes.